Pengaruh Mata Kuliah Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa - Astar, S Edi (Jurnal Teknologi dan Bisnis, 2020)
Unemployment become a serious problem in Indonesia which is difficult to overcome, the reason is population in Indonesia growing higher but the amount of employment is being stuck. Companies are being more selective to hiring new employees, but the entrepreneurship intention of young generation in Indonesia is still low. In this condition, education has a responsibility to increase the entrepreneurship intention of young generation. This research aims to know the influence of entrepreneurship course to student’s entrepreneuship intention. This is a descriptive reasearch using quantitative method. This research uses a probability sampling type of simple random sampling. Data were analyzed using descriptive analysis and multiple linear regression analysis. The results are : 1) Presented materials directly influence to entrepreneurship intention. 2) The way of delivering materials have no direct influence to student’s etrepreneurship intention. These results give a suggestion to the institution that have entrepreneurship course to increase their presented materials and the way they deliver the materials. And also give a knowledge to students how entrepreneurship course influence the student’s entrepreneurship intention.